The importance of environmental aspects of packaging - Jacqueline L. Spence; David A. Ogg (South African Journal of Business Management, 1994)
Increasing attention is being paid to packaging, a component of product in the marketing mix. It is being recognized that packaging is important not only from a functional viewpoint, but also in terms of marketing to the customer. One of the constraints on packaging is environmental Issues. These are becoming increasingly important internationally, from both a legislative and consumer perspective. In this study the perceptions of the members of the packaging value chain as regards the functional, marketing and environmental Issues surrounding packaging are examined. It is found that functional aspects appear to be the most important, followed by marketing aspects. Environmental concerns are rated as unimportant. This is despite evidence that these Issues should be regarded with increasing importance based on international trends. However, the relative importance of environmental packaging Issues is greatest amongst raw-material suppliers, followed by packaging and fast moving consumer goods (FMCG) suppliers. Retailers have the least interest.
Keywords: 650